Transforming forest landscape conflicts: the promises and perils of global forest management initiatives such as REDD+ - Seth Kane; Ahmad Dhiaulhaq; Lok Mani Sapkota; David Gritten (Forestry Faculty, Universitas Hasanuddin, 2018)
Implementation of Reducing Emissions from Deforestation and Forest Degradation (REDD+) is designed to relieve pressure on tropical forests, however, many are concerned that it is a threat to the rights of forest communities. These potential risks need serious attention as earlier studies have shown that the Asia-Pacific region is a forest conflict hotspot, with many economic, environmental and social implications at global (e.g. climate change) to local levels (e.g. poverty). Drawing on an analysis of nine case studies from four countries (Cambodia, Myanmar, Nepal and Vietnam) this paper examines why and how REDD+ can be a driver for forest conflict and how it also has the potential to simultaneously transform these conflicts. The analytical framework, “sources of impairment”, applied in the study was developed to increase understanding and facilitate the resolution of forest landscape conflicts in a sustainable manner (i.e. transformation). The main findings are that REDD+ can be a source of conflict in the study sites, but also had transformative potential when good practices were followed. For example, in some sites, the REDD+ projects were sources of impairment for forest communities by restricting access to forest resources. However, the research also identified REDD+ projects that enabled the participation of traditionally marginalized groups and built local forest management capacities, leading to strengthened tenure for some forest communities. Similarly, in some countries REDD+ has served as a mechanism to pilot Free, Prior and Informed Consent (FPIC), which will likely have significant impacts in mitigating conflicts by addressing the sources at local to national levels. Based on these findings, there are many reasons to be optimistic that REDD+ can address the underlying causes of forest landscape conflicts, especially when linked with other governance initiatives such as Forest Law Enforcement, Governance and Trade – Voluntary Participation Agreements (FLEGT-VPA).